2023
DOI: 10.3390/biomedicines11051241
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibodies Occurrence in Acute SARS-CoV-2 Infection without Overt Thrombosis

Abstract: We sought to determine the prevalence of antiphospholipid antibodies (aPLs) and their correlation with COVID-19 severity (in terms of clinical and laboratory parameters) in patients without thrombotic events during the early phase of infection. This was a cross-sectional study with the inclusion of hospitalized COVID-19 patients from a single department during the COVID-19 pandemic (April 2020–May 2021). Previous known immune disease or thrombophilia along with long-term anticoagulation and patients with overt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Another such correlation was observed by Cerbu et al in their study regarding patients with hepatitis, where, due to the liver impairment caused by the underlying condition, statistically significant differences were observed between patients with hepatitis and those without (56 mg/L vs. 12 mg/L) [ 44 ]. Other conditions correlated with CRP levels in SARS-CoV-2 infection are heart conditions according to Pilut et al and Tudoran et al [ 33 , 45 , 46 ], thromboembolic events due to lupus antibodies, as observed in a multivariate analysis by Dima et al (OR = 1.008, 95% CI: 1.001–1.016) [ 47 ], and type 2 diabetes according to Restea et al and Gradisteanu et al [ 48 , 49 ]. Another study from 2022 investigated a link between laboratory markers and features found on the Computer Tomography (CT) results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another such correlation was observed by Cerbu et al in their study regarding patients with hepatitis, where, due to the liver impairment caused by the underlying condition, statistically significant differences were observed between patients with hepatitis and those without (56 mg/L vs. 12 mg/L) [ 44 ]. Other conditions correlated with CRP levels in SARS-CoV-2 infection are heart conditions according to Pilut et al and Tudoran et al [ 33 , 45 , 46 ], thromboembolic events due to lupus antibodies, as observed in a multivariate analysis by Dima et al (OR = 1.008, 95% CI: 1.001–1.016) [ 47 ], and type 2 diabetes according to Restea et al and Gradisteanu et al [ 48 , 49 ]. Another study from 2022 investigated a link between laboratory markers and features found on the Computer Tomography (CT) results.…”
Section: Resultsmentioning
confidence: 99%
“…The major laboratory markers that were studied by Romanian authors are displayed in Table 1. Yes, even more so in Roma [53,54,[58][59][60][61][62]70] Diabetes [48,94] Antiphospholipid syndrome [47] Hypertension [27] Cardiac dysfunction [46,73,93] Overweight/metabolic syndrome [27,54,93] Lung involvement [50,57] PIMS [83] Chronic Spontaneous Urticaria Exacerbation [42] Pneumothorax/ pneumomediastinum [31,72] Liver failure [44] Multiple organ dysfunction [ [57,58,102,103] No [55] More comorbidities [29,101] Lung involvement [57] In addition, this article aimed to identify gaps in this research and provide encouragement for Romanian research to focus on novel and detailed aspects of the pandemic. For instance, as Romania grapples with the aftermath of the COVID-19 pandemic, understanding the long-term effects of the disease is of paramount importance.…”
Section: Discussionmentioning
confidence: 99%